The Determining Factors of Financial Culture, Financial Literacy and Financial Behavior - Csorba, László (Public Finance Quarterly, 2020)
Non-financial culture is a key factor in the field of economy, including in the operation of financial markets. Products of financial markets are characteristically mutually advantageous for all parties. Therefore, marginalizing of products for cultural reasons only will have adverse effects on economic development. In the last few years, measurement and development of financial education has become increasingly important. This writing introduces the basic fields of non-financial culture. The relevance of financial culture pertains to not only clients, but also, to players on the supply side. Despite of the fact that financial culture and financial literacy share some fields, both categories have separate and exclusive fields, too. In this context, values, beliefs, standards and attitudes shared by the community are exclusive to culture. Individual financial knowledge and attitudes are exclusive to financial literacy. Whether it is about the emergence and subsistence of individual or community attitudes, values – especially beliefs – play a key role. In the development of financial culture, beliefs and stereotypes must be factored in. At the same time, striving to allow for the emergence and reinforcement of new beliefs is also necessary. In these efforts, key roles are played by the supply side of financial markets, the Hungarian Central Bank, the Ministry of Finance, the State Audit Office of Hungary, and the education system in the widest sense possible.